(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to compare treatment outcomes using conventional titanium microplate and arch bar with 3- Dimensional titanium microplate in the management of pediatric anterior mandibular fractures. Study Design: Comparative / Prospective study Place and Duration of Study: This study was conducted at the department of pediatric Oral & Maxillofacial Surgery, The Children’s Hospital & Institute of Child Health, Lahore in 2018. Materials and Methods: A total number of 44pediatric patients were included in this study.Patients were randomly categorized into 2 groups. Group A comprised of patients with standard titanium microplate and arch bar while Group B patients were treated with 3-dimensional plate alone. Clinical parameters observed were, infection and assessment of intraoperative time for each plate fixation and infection. Results: After 1st week in Group A, infection was 32%, in Group B, only two (9%) patients showed infection. On 4th week infection rate was 18% in Group A and 4.5 % in Group B. At 12 weeks there was no sin of infection in both groups. Bony union was observed clinically by pain and tenderness and bridging of fracture gap on OPG. At the end of 12th week there was complete bridging of gap in both groups. Malocclusion was 13.6% in Group A. In Group B no case of malocclusion was observed. Mean intraoperative time for Group A was 109.5 ± 9.6 minutes and that of Group B was 53.5 ± 19.9 minutes (p<0.05). Conclusion: 3- Dimensional plate is a convenient and time saving alternate to conventional microplate and arch bar.